Answer:
k = 4
Step-by-step explanation:
Plug in the values of 2 for x and 0 for y, and solve for k.
2x + 3y = k
2(2) + 3(0) = k
4 = k
k = 4
Y=mx+b
b=y intercept
the current one is y=-2
6 units up is -2+6=4
new one is 4
Answer:
x = 6
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define Equation</u>
3 - 2x = -1.5x
<u>Step 2: Solve for </u><em><u>x</u></em>
- Add 2x on both sides: 3 = 0.5x
- Divide 0.5 on both sides: 6 = x
- Rewrite: x = 6
<u>Step 3: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in<em> x</em>: 3 - 2(6) = -1.5(6)
- Multiply: 3 - 12 = -9
- Subtract: -9 = -9
Here we see that -9 does indeed equal -9.
∴ x = 6 is the solution to the equation.
Its a , i had it yesterday and i got everything right dont worry :))
Answer:
It's answer is 1/3 .
Hope it helps have a great time :)